Proceedings ILASS–Europe 2017. 28th Conference on Liquid Atomization and Spray Systems 2017
DOI: 10.4995/ilass2017.2017.4661
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of nozzle surface bound fuel for diesel injectors

Abstract: In a fuel injector at the end of the injection, the needle descent and the rapid pressure drop in the nozzle leads to discharge of large, slow-moving liquid structures. This unwanted discharge is often referred as fuel 'dribble' and results in near-nozzle surface wetting, creating fuel-rich regions that are believed to contribute to unburnt hydrocarbon emissions. Subsequent fluid overspill occurs during the pressure drop in the expansion stroke when residual fluid inside the nozzle is displaced by the expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…6), suggesting that the fuel volumes estimated from our morphological reconstructions are consistent. In agreement with previously published studies [6,7], this investigation revealed a high cycle-to-cycle deviation in the quantity of fuel delivered after the end of injection. No clear dependence of the fuel dribble on injection pressure was observed (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…6), suggesting that the fuel volumes estimated from our morphological reconstructions are consistent. In agreement with previously published studies [6,7], this investigation revealed a high cycle-to-cycle deviation in the quantity of fuel delivered after the end of injection. No clear dependence of the fuel dribble on injection pressure was observed (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Recently published studies [6][7][8][9][10] demonstrate different aspects of the EOI fuel dribble based on a qualitative and quantitative analysis of experimental images of the injection process. The following important factors affecting the mechanism of the fuel dribble were studied: peak injection velocity [7], needle closing speed [7], in-cylinder pressure [6,7], injection pressure [6], fuel mass expulsion [9], bubble ingestion at the EOI [10], liquid length recession at the EOI [8] and different flow characteristics at the EOI [11]. The present study is dedicated to a quantitative analysis of the fuel dribble with the focus on dribble volumes estimated by processing of images from high-speed X-ray phase-contrast and diffused back-illumination (DBI) imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there are many unexplored fluid dynamic processes occurring in and around the injector nozzle at the macroscopic scale [33], our investigation is focused on the nozzle wetting processes that occur on the nozzle surface at the microscopic scale, as the cycle progresses. Our previous work confirmed that fuel would deposit and spread on the surface of the injector nozzle through both the impingement of fuel droplets and the overspill of nozzle-trapped liquid fuel [26,27]. The investigations were performed on a 2-stroke reciprocating rapid compression machine (RRCM), therefore the 4-stroke optical diesel engine utilised here provides further validation of the conclusions previously drawn and introduces the interactions of realistic in-cylinder gas flow.…”
Section: Introductionsupporting
confidence: 68%
“…Although the approximated peak ICT is 439 K (still below the octane vapour saturation temperature at 45 CAD), the nozzle surface temperature would be much lower than this due to thermal inertia, the relatively short period of maximum ICT, and the engine head temperature of around 358 K [37,38]. During a previous investigation we measured the nozzle tip temperature with an embedded K-type thermocouple inside a 6-hole Siemens VCO injector [27]. The experiments were carried out in a motored reciprocating rapid compression machine with an engine speed of 500 rpm.…”
Section: The Expansion Strokementioning
confidence: 99%
See 1 more Smart Citation